Cardiac rhabdomyomata and megacystis-microcolon-intestinal hypoperistalsis syndrome. - Couper, R T (1991)
Multiple cardiac rhabdomyomata were discovered on necropsy tissue review of a previously well child with megacystis-microcolon-intestinal hypoperistalsis syndrome, who died unexpectedly at home at 40 months of age. Multiple cardiac rhabdomyomata occur rarely and have not previously been reported with this syndrome. They are most frequently associated with tuberous sclerosis. The finding of multiple cardiac rhabdomyomata in this patient suggests the possibility that these two rare conditions may be associated. Putative gene loci for tuberous sclerosis have been assigned to the long arms of chromosomes 9 and 11 and it is possible that the cardiac rhabdomyomata seen in this patient are a serendipitous indicator of the location of the megacystis-microcolon-intestinal hypoperistalsis gene.